CIRCULAR ECONOMY MODELS IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The aim of the article is to identify the essence of the circular economy (CE) and to develop business models for its use to reduce environmental impact. It is established that the essence of the economic system lies in the self-accumulation of capital by increasing the mass of recycled resources and the speed of their circulation in the production process. To ensure its functioning, such a system absorbs new territories, sources of raw materials, energy, and human resources. The linear model of economic growth can no longer meet the needs of modern society. It has been proven that in a circular economy, the value of products and materials is preserved much longer, resource use efficiency is increased, and waste is minimized. When a product reaches the end of its life cycle, resources remain in the economy for the creation of additional value. These models not only create safe jobs but also introduce innovations that provide a competitive advantage and a high level of protection for the population and the environment. Additionally, the CE model provides consumers with more durable and innovative products that help save money and improve quality of life. Based on the principles in the waste management hierarchy from 4R (reduce, reuse, recycle, repurpose) through 5Rs (refuse, reduce, reuse, repurpose, recycle) to 9Rs and 12Rs of zero waste, business models have been identified that implement the ideas of the circular economy at the micro (products, enterprises, consumers), meso (eco-industrial parks), and macro levels (city, region, nation). It has been substantiated that in a circular economy, the value of products and materials is preserved much longer, resource use efficiency is increased, and waste is minimized. When a product reaches the end of its life cycle, resources remain in the economy for the creation of additional value. These models not only create safe jobs but also introduce innovations that provide a competitive advantage and a high level of protection for the population and the environment. The CE model provides consumers with more durable and innovative products that help save money and improve quality of life.
Keywords: economic system, circular economy, linear model of economic growth, Sustainable Development Goals, financing of circular business projects, circular economy strategy of Ukraine.